DNase I hypersensitive regions correlate with a site-specific endogenous nuclease activity on the r-chromatin of Tetrahymena. - Bonven, B (1982)
A novel nuclease activity have been detected at three specific sites in the chromatin of the spacer region flanking the 5'-end of the ribosomal RNA gene from Tetrahymena. The endogenous nuclease does not function catalytically in vitro, but is in analogy with the DNA topoisomerases activated by strong denaturants to cleave DNA at specific sites. The endogenous cleavages have been mapped at positions +50, -650 and -1100 relative to the 5'-end of the pre-35S rRNA. The endogenous cleavage sites are associated with micrococcal nuclease hypersensitive sites and DNase I hypersensitive regions. Thus, a single well-defined micrococcal nuclease hypersensitive site is found approximately 130 bp upstream from each of the endogenous cleavages. Clusters of defined sites, the majority of which fall within the 130 bp regions defined by vicinal micrococcal nuclease and endogenous cleavages, constitute the DNase I hypersensitive regions.